Difficulty in performing everyday activities in patients with juvenile macular dystrophies: comparison with patients with retinitis pigmentosa. Issue 12 (1st December 1998) - Szlyk, Janet P; Fishman, Gerald A; Grover, Sandeep; Revelins, Beatrise I; Derlacki, Deborah J
Abstract : AIMS: To ascertain the level of perceived difficulty experienced by patients with central vision loss due to juvenile macular dystrophies in the performance of everyday activities. A second objective was to compare their perceived difficulty with that of patients with retinitis pigmentosa (RP) with primarily peripheral vision loss. METHODS: 72 patients with Stargardt disease, cone dystrophy, or cone-rod dystrophy who had visual acuities worse than 20/40 and normal peripheral visual fields rated themselves on their difficulty in the performance of 33 activities encompassing a wide variety of everyday tasks. These findings were compared with the responses of 120 patients with typical RP or Usher syndrome type 2 who had visual acuities of 20/40 or better and peripheral visual field loss. RESULTS: The juvenile macular dystrophy group reported the greatest level of overall self perceived difficulty with activities involving central vision, and lesser and variable degrees of difficulty with items within the mobility, negotiating steps, driving, and miscellaneous categories. Consistent with these findings, there were highly significant correlations between subjects' rated performances of activities involving central vision and the clinical measures of vision, including visual acuity and size of central scotoma. There were fewer significant correlations between perceived performance of activities in the other categories and the clinical measures. In general, those activities that showed significant correlations with the clinical measures of vision for the patients with juvenile macular dystrophies also showed significant differences in the patterns of responses between the juvenile macular dystrophy group and the RP group. Those items which were not correlated with the clinical measures in the juvenile macular dystrophy group tended not to show significant differences in the response patterns between the two groups. CONCLUSION: These results provide insight into the types of perceived difficulties in performing tasks of everyday life in patients with these disorders which affect counselling of these patients.